Week 96 extension results of a Phase 3 study evaluating long-acting cabotegravir with rilpivirine for HIV-1 treatment. (1st February 2022) - Swindells, Susan; Lutz, Thomas; Van Zyl, Lelanie; Porteiro, Norma; Stoll, Matthias; Mitha, Essack; Shon, Alyssa; Benn, Paul; Huang, Jenny O.; Harrington, Conn M.; Hove, Kai; Ford, Susan L.; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Background: ATLAS (NCT02951052), a phase 3, multicenter, open-label study, demonstrated that switching to injectable cabotegravir (CAB) with rilpivirine (RPV) long-acting dosed every 4 weeks was noninferior at week (W) 48 to continuing three-drug daily oral current antiretroviral therapy (CAR). Results from the W 96 analysis are presented. Methods and design: Participants completing W 52 of ATLAS were given the option to withdraw, transition to ATLAS-2M (NCT03299049), or enter an Extension Phase to continue long-acting therapy (Long-acting arm) or switch from CAR to long-acting therapy (Switch arm). Endpoints assessed at W 96 included proportion of participants with plasma HIV-1 RNA less than 50 copies/ml, incidence of confirmed virologic failure (CVF; two consecutive HIV-1 RNA ≥200 copies/ml), safety and tolerability, pharmacokinetics, and patient-reported outcomes. Results: Most participants completing the Maintenance Phase transitioned to ATLAS-2M (88%, n  = 502/572). Overall, 52 participants were included in the W 96 analysis of ATLAS; of these, 100% ( n  = 23/23) and 97% ( n  = 28/29) in the Long-acting and Switch arms had plasma HIV-1 RNA less than 50 copies/ml at W 96, respectively. One participant had plasma HIV-1 RNA 50 copies/ml or higher in the Switch arm (173 copies/ml). No participants met the CVF criterion during the Extension Phase. No new safety signals were identified. All Switch arm participants surveyed preferred long-acting therapy to their previous daily oral regimen (100%, n  = 27/27). Conclusion: In this subgroup of ATLAS, 98% ( n  = 51/52) of participants at the Extension Phase W 96 analysis maintained virologic suppression with long-acting therapy. Safety, efficacy, and participant preference results support the therapeutic potential of long-acting CAB+RPV treatment for virologically suppressed people living with HIV-1.